2012
DOI: 10.1007/s10858-012-9645-2
|View full text |Cite
|
Sign up to set email alerts
|

The J-UNIO protocol for automated protein structure determination by NMR in solution

Abstract: The J-UNIO (JCSG protocol using the software UNIO) procedure for automated protein structure determination by NMR in solution is introduced. In the present implementation, J-UNIO makes use of APSY-NMR spectroscopy, 3D heteronuclear-resolved [1H,1H]-NOESY experiments, and the software UNIO. Applications with proteins from the JCSG target list with sizes up to 150 residues showed that the procedure is highly robust and efficient. In all instances the correct polypeptide fold was obtained in the first round of au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
135
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
8

Relationship

8
0

Authors

Journals

citations
Cited by 57 publications
(136 citation statements)
references
References 35 publications
1
135
0
Order By: Relevance
“…The NOE data were measured at 800 MHz or 1 GHz with a mixing time of 80 ms. The three NOESY spectra were peak picked and assigned automatically with the standard ATNOS/CANDID/CYANA protocol including seven cycles of peak picking, NOE assignment, and three-dimensional structure calculation with simulated annealing in torsion angle space (26). The final target function was 2.6 Å 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The NOE data were measured at 800 MHz or 1 GHz with a mixing time of 80 ms. The three NOESY spectra were peak picked and assigned automatically with the standard ATNOS/CANDID/CYANA protocol including seven cycles of peak picking, NOE assignment, and three-dimensional structure calculation with simulated annealing in torsion angle space (26). The final target function was 2.6 Å 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The software UNIO-ATNOS/CANDID 28,29 was used in combination with the torsion angle dynamics algorithm CYANA3.0 30 in a standard seven-cycle protocol for NOESY peak picking, NOE assignment and structure calculation. 31 The intensities from the NOEs were converted into distance restraints and combined with the backbone dihedral angles derived from TALOS, 27 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 17.5K. Dynamic exclusion was enabled for 90 s. …”
Section: Methodsmentioning
confidence: 99%
“…Out of the six assigned side chain amides, two isolated NH 2 groups of N64 and N74 are labelled. Regular secondary structure elements of CHD1C were identified from 13 C ab secondary shifts, which were calculated as previously described (Serrano et al 2012), and are reported in Fig. 2 Fig.…”
Section: Assignments and Data Depositionmentioning
confidence: 99%